Fetal agenesis of corpus callosum: chromosomal copy number abnormalities and postnatal follow-up - Meiying Cai; Na Lin; Meimei Fu; Yanting Que; Hailong Huang; Liangpu Xu (Molecular Biology Reports, 2024)
Objective Agenesis of the corpus callosum (ACC) is an anomaly that can occur in fetuses during pregnancy. However, there is currently no treatment for fetal ACC. Therefore, we conducted a retrospective analysis of obstetric outcomes of fetal ACC to explore the relationship between fetal ACC phenotypes and chromosomal copy number abnormalities. Methods and results Amniotic fluid or umbilical cord blood were extracted from pregnant women with fetal ACC for karyotype analysis and chromosomal microarray analysis (CMA). Among the 48 fetuses with ACC, 22 (45.8%, 22/48) had isolated ACC, and 26 (54.2%, 26/48) had non-isolated ACC. Chromosomal abnormalities were detected via karyotype analysis in four cases. In addition to the four cases of pathogenic copy number variations (CNVs) detected using karyotype analysis, CMA revealed two cases of pathogenic CNVs with 17q12 microduplication and 16p12.2 microdeletion. The obstetric outcomes of 26 patients with non-isolated ACC were followed up, and 17 chose to terminate the pregnancy. In addition, seven of the nine cases with non-isolated ACC showed no obvious abnormality during postnatal follow-up, whereas only one case with normal CMA showed an abnormal phenotype at six months. Of the 22 patients with isolated ACC, six chose to terminate the pregnancy. Postnatal follow-up of 16 isolated ACC cases revealed only one with benign CNV, presenting with intellectual disability. Conclusion Pregnant women with fetal ACC should be offered prenatal CMA, particularly non-isolated ACC. Patients with ACC should undergo prolonged postnatal follow-up, and appropriate intervention should be provided if necessary.